Analysis of Welded Joint Properties on an AISI316L Stainless Steel Tube Manufactured by SLM Technology - Mohyla, Petr; Hajnys, Jiri; Sternadelová, Kristýna; Krejčí, Lucie; Pagáč, Marek; Konečná, Kateřina; Krpec, Pavel (Materials (Basel, Switzerland), 2020)
This work is focused on the analysis of the influence of welding on the properties and microstructure of the AISI316L stainless steel tube produced by 3D printing, specifically the SLM (Selective Laser Melting) method. Both non-destructive and destructive tests, including metallographic and fractographic analyses, were performed within the experiment. Microstructure analysis shows that the initial texture of the 3D print disappears toward the fuse boundary. It is evident that high temperature during welding has a positive effect on microstructure. Material failure occurred in the base material near the heat affected zone (HAZ). The results obtained show the fundamental influence of SLM technology in terms of material defects, on the properties of welded joints.
Keywords: mechanical properties; microstructure; selective laser melting; welded joints